PENGGUNAAN MODEL PEMBELAJARAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATIC (STEM) PADA KONSEP ASAM BASA DI SMAN 1 BAITUSSALAM - Haris Munandar; Lia Maghfira Izzani; Muammar Yulian (UIN AR-RANIRY, 2019)
Based on observations at SMAN 1 Baitussalam, information was obtained that learning outcomes of students on acid-base material were still low, this was caused by the process of learning chemistry that was still teacher-centered and didn’t use specific learning models. The STEM learning model is a One learning model that can be used as solution to this problem is the learning model of Science, Technology, Engineering, and Mathematics (STEM). The purpose of this study was to obtain information about the effect of the STEM learning model on learning outcomes and student responses, especially on the concept of acid-base in SMAN 1 Baitussalam. This study uses Quasi Experimental design, with data collected through test and questionnaires. Student test results were analyzed using SPSS Version 23.0, where the significance value obtained from the t-test analysis was 0,000<0.05 so it can be seen that Ho was rejected and Ha was accepted. Student responses obtained through questionnaires analyzed based on the percentage answers provided by students, the results showed that 93% responses of students were very interested in the STEM learning model. These results indicate that STEM learning model is effective in improving student learning outcomes in SMAN 1 Baitussalam, especially in acid-base concept.